Flavonolignan 2,3-dehydrosilydianin activates Nrf2 and upregulates NAD(P)H:quinone oxidoreductase 1 in Hepa1c1c7 cells - Roubalová, Lenka; Dinkova-Kostova, Albena T; Biedermann, David; Křen, Vladimír; Ulrichová, Jitka; Vrba, Jiří (Fitoterapia, 2017)
Silybum marianum (milk thistle) is a medicinal plant used for the treatment of various liver disorders. This study examined whether the main flavonolignans from S. marianum (i.e. silybin, silychristin, silydianin) and their 2,3-dehydro derivatives (i.e. 2,3-dehydrosilybin, 2,3-dehydrosilychristin, 2,3-dehydrosilydianin) activate the Nrf2 pathway, which regulates the expression of genes encoding many cytoprotective enzymes, including NAD(P)H:quinone oxidoreductase 1 (NQO1). After 48h of exposure, 2,3-dehydrosilydianin at concentrations of 25μM and higher significantly elevated the activity of NQO1 in murine hepatoma Hepa1c1c7 cells. In contrast, other tested compounds at non-cytotoxic concentrations had a mild or negligible effect on the NQO1 activity. Using a luciferase reporter assay, 2,3-dehydrosilydianin was found to significantly activate transcription via the antioxidant response element in stably transfected human AREc32 reporter cells. Moreover, 2,3-dehydrosilydianin caused the accumulation of Nrf2 and significantly induced the expression of the Nqo1 gene at both the mRNA and protein levels in Hepa1c1c7 cells. We found that 2,3-dehydrosilydianin also increased to some extent the expression of other Nrf2 target genes, namely of the heme oxygenase-1 gene (Hmox1) and the glutamate-cysteine ligase modifier subunit gene (Gclm). We conclude that 2,3-dehydrosilydianin activates Nrf2 and induces Nrf2-mediated gene expression in Hepa1c1c7 cells.
Keywords: silymarin; lidé; hemoxygenasa-1; faktor 2 související s NF-E2; Heme Oxygenase-1; upregulace; Gene Expression; Cell Line, Tumor; molekulární struktura; ostropestřec mariánský; myši; Humans; Mice; NAD(P)H dehydrogenasa (chinon); Glutamate-Cysteine Ligase; Molecular Structure; glutamátcysteinligasa; membránové proteiny; zvířata; Silybum marianum; NAD(P)H Dehydrogenase (Quinone); Membrane Proteins; Animals; exprese genu; nádorové buněčné linie; NF-E2-Related Factor 2; Up-Regulation; Silymarin